2011
DOI: 10.1002/ps.2135
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of a self‐propelled sprayer and effects of the application rate on spray deposition and losses to the ground in greenhouse tomato crops

Abstract: The vertical spray booms used in tomato crops improve the application of plant protection products with respect to the spray gun, reducing the application volumes and the environmental risks of soil pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 17 publications
10
37
0
Order By: Relevance
“…In this last case, PI values ranged from 26.1 to 50%; this indicates that in some part of the canopy the spray liquid retained by the leaves was only a quarter of the total deposited in the external part of the canopy. This fact directly relates to the efficacy of applying a certain spray, in terms of pest/disease control, as already reported by Sánchez‐Hermosilla et al …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this last case, PI values ranged from 26.1 to 50%; this indicates that in some part of the canopy the spray liquid retained by the leaves was only a quarter of the total deposited in the external part of the canopy. This fact directly relates to the efficacy of applying a certain spray, in terms of pest/disease control, as already reported by Sánchez‐Hermosilla et al …”
Section: Discussionsupporting
confidence: 63%
“…Self‐propelled and autonomous sprayers have also attracted interest because of reduced operator exposure, improved work capacity and in some cases reduced application of PPPs while maintaining the efficacy of pest/disease control . However, problems have also been reported: poor penetration capacity exhibited by vertical boom sprayers without air assistance; management of hand‐held trolleys depending on the soil type and sprayer design; difficulties of identifying accurate conditions for safe and efficient use of self‐propelled sprayers, including aspects related to the high level of investment required …”
Section: Introductionmentioning
confidence: 99%
“…discovered that the amount of water (4.7–14.1 L ha −1 ) did not affect the efficacy of the product and advised that more acres per load be treated by reducing the spray rate. In terms of large volume ground application, Sánchez‐Hermosilla et al . reduced application volumes from 1000 to 500 L ha −1 and improved crop control product application in tomato by altering the spray gun (900 and 1800 L ha −1 ) on the vertical spray boom.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies the values of d v and  have been calculated in a greenhouse tomato crops (Cerruto et al, 2009a, b;Sánchez-Hermosilla et al, 2011, as indicated in Table 3. In consideration of these values, our proposal is to use a value of 1.5 µL cm -2 d v and, for the spray fraction deposited on the canopy () 0.50 for spray-gun applications or 0.75 for spray boom applications.…”
Section: Development Of the Model To Estimate The Laimentioning
confidence: 99%